Investigating the effects of glucose and lipid metabolism on neuronal structure using optical coherence tomography in treatment-resistant schizophrenia - Yeşilkaya, Ümit Haluk; Şahmelikoğlu Onur, Özge; Akarsu Acar, Özge Pınar; Göy, Defne Flora; Onur, İsmail Umut; Karamustafalıoğlu, Nesrin (Kare Publishing, 2023)
Objective:The effects of metabolic changes on neural structures in the later stages of schizophrenia remain unknown. Alterations in glucose and lipid metabolism could impact disease progression. This study aims to investigate the effects of glucose and lipid metabolism on neuronal structures in treatment-resistant schizophrenia using optical coherence tomography (OCT), glycogenic proteins, and cholesterol values.Method:The study included 39 schizophrenia patients with remission, 43 treatment-resistant schizophrenia (TRS) patients, and 40 healthy controls (HC). Optical coherence tomography (OCT) was performed on all participants. Serum samples were collected to determine fasting glucose, Low-Density Lipoprotein (LDL), High-Density Lipoprotein (HDL), triglycerides, total cholesterol, fasting insulin, and Insulin-like Growth Factor 1 (IGF-1) levels. Results: IGF-1 levels in TRS patients were higher than those in the remission group. Additionally, the thickness of the inferior retinal nerve fiber layer (RNFL), superior RNFL, and global RNFL regions was significantly lower in the TRS group than in the HC group.Conclusion: While OCT measurements and elevated IGF-1 levels indicate neural thinning in treatment-resistant schizophrenia, there was no observed effect from lipid and glucose metabolism on this phenomenon.
Keywords: Glucose Metabolism; Lipid Metabolism; Neurodegeneration; OCT; Treatment-Resistant Schizophrenia